Study of Atmospheric Dynamics during the Quasi-Linear Convective System Event in West Sumatra (Case Study of March 11, 2025) - Karmelita Asri Widyandaru; Panji Kuswanaji; Ahmad Irsyad Saputra; Achmad Zakir; Aditya Mulya (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2026)
Quasi-Linear Convective System (QLCS) is an organized quasi-linear convective cloud structure that produces heavy rainfall. This study uses a single explanatory case study method on QLCS that occurred in West Sumatra on 11 March 2025. This study aims to explain the atmospheric dynamic mechanisms in convective system formation and their relationship with rainfall. Doppler C-Band weather radar data from the Padang Meteorological Station were used to analyze QLCS using Lombardo and Colle (2010) criteria. Radar products, including Column Maximum Reflectivity (CMAX) and Surface Rainfall Intensity (SRI), along with ERA5 reanalysis data, were used to examine cloud structure, rainfall intensity, and supporting atmospheric conditions. QLCS had length of 56.81 km, width 8.10 km, maximum reflectivity of 53 dBZ, and 60 minutes lifetime. The system developed due to low-level wind convergence supported by unstable atmospheric conditions, indicated by moderate to high Convective Available Potential Energy (CAPE) values (1000–2000 J kg⁻¹), upward air motion in 700–400 hPa layer, and high mid-level humidity. During the mature phase, QLCS produced heavy rainfall with a maximum intensity of 51 mm/hour. This study contributes to the scientific understanding of the relationship between atmospheric dynamics and regional mitigation efforts by examining rainfall associated with QLCS events.